Out of sight, out of mind... Cairo's street children: a question of agency and justice - Wang, Shirley (AUC Knowledge Fountain, 2013)
This thesis explores how the Convention of the Rights of the Child (CRC) is translated into Egypt’s national law and examines the practical applications of the law via programs and services provided by nongovernmental organizations (NGOs) when tackling the street child phenomenon. The first part of this thesis is focused on critically examining the theoretical and philosophical implications of the construction of the “child” and “adult”, and its subsequent effects on the regulation of the human body, agency and contemporary justice. The usage of language is important as it is closely linked with the contemporary notion of justice in relation to the CRC. By deconstructing the terms “child” and “adult”, I try to complicate and challenge the ways in which we understand the dichotomy and how we engage with these labels. I argue that the current theoretical and philosophical implications of child and adult as elaborated in the CRC perpetuate negative repercussions on the concept of justice, while simultaneously paving way for programs and services that both perpetuate and defy the child-adult dichotomy. The second part of this thesis examines how the CRC has been implemented into practice via NGOs in Egypt when dealing with street children. Although there are many NGOs working in Egypt, I have chosen to engage with Plan Egypt. The focus of my analyses is on the methods and implications of projects and services provided and the differences in the treatment and availability of programs for street girls and boys. Through observations and interviews, I explore how the organization both contribute and defy the contemporary manifestation of justice in relation to the State and law. Lastly, through this analytical engagement, I try and understand the current function and role of contemporary justice, as manifested in both State legislation and in programs and services offered by Plan Egypt when addressing street children. By examining pre- and post-January 25th online published news articles, I argue that although these frameworks allow street children some room for agency. However, the ultimate outcome of contemporary justice goes beyond the perpetuation of the child-adult dichotomy and into the realms of governmentality and biopolitics of all individuals.